Measurement of Very Fast Exchange Rates of Individual Amide Protons in Proteins by NMR Spectroscopy. Issue 2 (18th December 2018) - Dass, Rupashree; Corlianò, Enrico; Mulder, Frans A. A.
Abstract: NMR spectroscopy is a pivotal technique to measure hydrogen exchange rates in proteins. However, currently available NMR methods to measure backbone exchange are limited to rates of up to a few per second. To raise this limit, we have developed an approach that is capable of measuring proton exchange rates up to approximately 10 4  s −1 . Our method relies on the detection of signal loss due to the decorrelation of antiphase operators 2Nx Hz by exchange events that occur during a series of pi pulses on the 15 N channel. In practice, signal attenuation was monitored in a series of 2D H(CACO)N spectra, recorded with varying pi‐pulse spacing, and the exchange rate was obtained by numerical fitting to the evolution of the density matrix. The method was applied to the small calcium‐binding protein Calbindin D9k, where exchange rates up to 600 s −1 were measured for amides, where no signal was detectable in 15 N− 1 H HSQC spectra. A temperature variation study allowed us to determine apparent activation energies in the range 47–69 kJ mol −1 for these fast exchanging amide protons, consistent with hydroxide‐catalyzed exchange. Abstract : New spin ! We present a novel method to measure very high amide proton exchange rates up to approximately 10 4  s −1 in a small protein, where the exchanging protons are undetectable in 15 N− 1 H HSQC experiments.